Conocimientos tradicionales sobre Brosimum alicastrum y hongos comestibles del bosque seco premontano tropical en la Comunidad Kichwa San Juan de Miraflores, San Martín - Lopez Alvarez, Chris Anggello (2024)
The present research, titled “Traditional knowledge about Brosimun Alicastrum and edible mushrooms from the tropical premontane dry forest in the San Juan de Miraflores Kichwa community, San Martín 2023” was carried out in the district of San Pablo, province of Bellavista, department of San Martín. Its main objective is to describe the traditional knowledge of Brosimum alicastrum and edible mushrooms from the dry tropical premontane forest in the native Kichwa community of San Juan de Miraflores. In accordance with the research methodology, it presents a qualitative approach, descriptive and ethnographic design. The instruments and data collection techniques that were applied in the field were surveys, semi-structured interviews and participant observation. The population is made up of 43 people (21 men and 22 women). As for the sample, it consisted of 20 people (12 men and 8 women) aged 28 to 76 years. All informants demonstrate that they have traditional knowledge about the manchinga tree (B. alicastrum) and edible mushrooms. The results of this research demonstrated the significant importance of this complex traditional knowledge and how it directly influences the well-being of the population.